Tennis forehand kinematics change as post-impact ball speed is altered - Seeley, M. K.; Funk, M. D.; Denning, W. M.; Hager, R. L.; Hopkins, J. T. (Sports Biomechanics, 2011)
Peak joint angles and joint angular velocities were evaluated for varying speed forehands in an attempt to better understand what kinematic variables are most closely related to increases in post-impact ball velocity above 50% of maximal effort. High-speed video was used to measure three-dimensional motion for 12 highly skilled tennis players who performed forehands at three different post-impact ball speeds: fast (42.7 ± 3.8 m/s), medium (32.1 ± 2.9 m/s), and slow (21.4 ± 2.0 m/s). Several dominant-side peak joint angles (prior to ball impact) increased as post-impact ball speed increased from slow to fast: wrist extension (16%), trunk rotation (28%), hip flexion (38%), knee flexion (27%), and dorsiflexion (5%). Between the aforementioned peak joint angles and ball impact, dominant-side peak angular velocities increased as ball speed increased from slow to fast: peak wrist flexion (118%), elbow flexion (176%), trunk rotation (99%), hip extension (143%), knee extension (56%), and plantarflexion (87%). Most kinematic variables changed as forehand ball speed changed; however, some variables changed more than others, indicating that range of motion and angular velocity for some joints may be more closely related to post-impact ball speed than for other joints.